Effects of excessive body fat on colostrum lipid patterns: overweight/obese vs. normal weight mothers - Qian Liu; Yan Liu; Di Yang; Yanpin Liu; Yan Liu; Weicang Qiao; Juncai Hou; Yaling Wang; Minghui Zhang; Kai Yang; Xiaofei Fan; Ziqi Li; et al. (Food Science and Human Wellness)
Prenatal overweight/ obesity (OW/ OB) can alter colostrum lipid patterns, thereby affecting the lipid metabolism and even the cognitive and healthy development of infants. However, studies on changes in colostrum lipids in the context of OW/OB are limited, particularly for glycerides and polar lipids. Therefore, this study investigated the influence of maternal prenatal weight on colostrum in lipid subclasses and molecular species. The concentration of triacylglycerols (TAGs) in the colostrum of the OW/OB group (35894.43 mg/L) was higher than that of the normal weight (NW) group (26639.20 mg/L), suggesting that colostrum from OW/OB mothers could provide more energy to their infants. Further analysis of the fatty acid composition of TAGs revealed that elevated maternal body weight enhanced the concentration of TAGs containing saturated or n-6 fatty acids and shortened the carbon number of TAGs. Docosahexaenoic acid (DHA)/arachidonic acid (AA)/choline-containing lipids, such as DHA-containing TAGs, AA/DHA-containing phosphatidylethanolamine, and choline-containing phospholipids, were present in higher levels in the colostrum of OW/OB mothers than NW mothers. However, the concentrations of palmitic acid-containing TAGs, linoleic acid-containing TAGs, dihomo-γ-linolenic acid-containing TAGs, and polar lipids and the ratio of TAGs containing n-6 fatty acid/n-3 fatty acid were significantly higher in the colostrum of OW/OB mothers than in that of NW mothers. The fatty acid composition and sphingoid bases of sphingolipids were also altered due to elevated body weight. In conclusion, OW/OB affects colostrum lipids with respect to composition, concentration, and percentage. Although the colostrum of healthy OW/OB mothers can provide sufficient DHA/AA/choline-containing lipids to their infants, normalization of body weight and fat reserves should be considered as a strategy for high-quality human milk lipids.